Cyrena2
contestada

After simplifying the following expression, the coefficient of the m^2 term will be ______.
6mn^2 + 3m^2 + 16m^2 - 6m^2 - 5nm^2
The solution is ______

Respuesta :

Answers:

After simplifying the following expression, the coefficient of the m^2 term will be  13  

The solution is  13m^2 + 6mn^2 - 5nm^2  

====================================================

Explanation:

Highlight all the terms that have m^2 in them and nothing else (so that means no variables of n or n^2)

You should highlight 3m^2, 16m^2 and -6m^2 as the three terms.

The coefficients 3, 16 and -6 combine to 3+16-6 = 13

Meaning that 3m^2+16m^2-6m^2 = 13m^2

----------------

There are no other like terms that pair up.

The 6mn^2 and -5nm^2 are different because the exponent 2 is over a different letter each time. Put another way: mn^2 is not the same as nm^2

So we cannot combine 6mn^2-5nm^2. We leave it as is.

Overall, the entire expression simplifies to 13m^2 + 6mn^2 - 5nm^2